2015
DOI: 10.1007/s11837-015-1483-8
|View full text |Cite
|
Sign up to set email alerts
|

High-Zinc Recovery from Residues by Sulfate Roasting and Water Leaching

Abstract: An integrated process for the recovery of zinc that is generated from zinc hydrometallurgy in residues was developed. A mixture of residue and ferric sulfate was first roasted to transform the various forms of zinc in the residue, such as ferrite, oxide, sulfide, and silicate, into zinc sulfate. Next, water leaching was conducted to extract the zinc while the iron remained in the residue as ferric oxide. The effects of the roasting and leaching parameters on zinc recovery were investigated. A maximum zinc reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The recovery rate of zinc reaches 99% at 600 °C and then gradually decreases with the temperature increase. Therefore, it can be stated clearly that sulfating of zinc minerals in ZPR, namely, zinc ferrite, zinc oxide, zinc sulfide and zinc silicate, are possible almost completely according to the reaction (4), as well as the following reactions [ 42 ]: ZnS (s) + 2O 2(g) = ZnSO 4(s) ZnO (s) + SO 3(g) = ZnSO 4(s) Zn 2 SiO 4(s) + 2SO 3(g) = 2ZnSO 4(s) + SiO 2(s) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery rate of zinc reaches 99% at 600 °C and then gradually decreases with the temperature increase. Therefore, it can be stated clearly that sulfating of zinc minerals in ZPR, namely, zinc ferrite, zinc oxide, zinc sulfide and zinc silicate, are possible almost completely according to the reaction (4), as well as the following reactions [ 42 ]: ZnS (s) + 2O 2(g) = ZnSO 4(s) ZnO (s) + SO 3(g) = ZnSO 4(s) Zn 2 SiO 4(s) + 2SO 3(g) = 2ZnSO 4(s) + SiO 2(s) …”
Section: Resultsmentioning
confidence: 99%
“…The main advantages are relatively low roasting temperature range, lack of fuel consumption due to exothermic sulfating reactions [ 41 ], the application of water leaching rather than acid leaching after the roasting to extract zinc and other valuable components. Some authors have studied iron sulfates as sulfating agents for roasting of zinc ferrite residues [ 42 , 43 ], copper slag [ 44 , 45 ], copper tailings [ 46 , 47 ] and electric arc furnace dust from steelmaking [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc slag therefore provides an important source of indium. [7][8][9] Several processes have been proposed for recovering indium from zinc slag. Dai et al 10 reported a process for extracting indium that involved neutral leaching, concentrated sulfuric acid curing leaching, and alkali leaching; a 99.7% indium leaching ratio was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have studied methods of sulphatizing of ZLR by roasting with elemental sulfur in air [16], with oleum [17], with sulphuric acid [18,19]. In recent years some authors have tested iron sulphates FeSO4 and Fe2(SO4)3 as sulphatizing agents for ZLR roasting [20,21]. In this paper, we consider characteristics of the approach of ZLR sulphatizing roasting in the presence of iron sulphates in order to convert zinc and copper compounds into the water-soluble sulphate form, and transform iron into water-insoluble form.…”
Section: Introductionmentioning
confidence: 99%